Respuesta :

Answer:

[tex]Equation : \\(x+3)^2 + ( y -2)^2 = 36[/tex]

Step-by-step explanation:

For standard form the circle's equation we need the centre of the circle and the radius.

Step 1: Find the centre

If the centre is not given find the end points of the diameter

and then find the mid point.

Let the end points of the diameter be : ( - 3 , 8 ) and ( -3 , -4 )

The mid-point of the diameter is :

                        [tex]Mid-point = (\frac{-3 + - 3}{2}, \frac{-4+8}{2}) = (-3, 2)[/tex]

Therefore, centre of the circle = ( -3 , 2 )

Step 2 : Find radius

[tex]Radius = \frac{Diameter }{2}[/tex]

Diameter is the distance between the end points ( -3 , 8) and ( -3 , -4 )

That is ,

 [tex]Diameter = \sqrt{(-3-(-3))^2 + ( -4 -8)^2}\\[/tex]

                 [tex]= \sqrt{(-3 + 3)^2 + (-12)^2}\\\\=\sqrt{0 + 144}\\\\=12[/tex]

Therefore ,

       [tex]Radius = \frac{12}{2} = 6[/tex]

Step 3 : Equation of the circle

Standard equation of the circle with centre ( h ,k )

and radius ,r is :

       [tex](x - h)^2+(y -k)^2 = r^2[/tex]

Therefore, the equation of the circle with centre ( -3, 2)

and radius = 6 is :

    [tex](x - (-3))^2 + (y - 2)^2 = 6^2\\\\(x + 3)^2 + (y - 2)^2 = 36[/tex]

ACCESS MORE